Hiperactividad en el proceso de desarrollo aprendizaje significativo de los niños de 3 a 4 años - Camacho Camacho, Patricia Isabel (2021)
This is a case study as an objective To determine the influence of hyperactivity in the adaptation process of children from 3 to 4 years old, but how many teachers report that it is a direct influence of the direct path in the educational process that they choose modify its methods at the end of which the baby is not affected. Part of the methodology is to establish a sample of relatives and some other students who are part of the institution "CDI" Rayitos; Proceed with the application of this to the parents who valued as all the words that pose the symptoms of ADHD such as bleeding, hyperactivity, impulsivity, in which it is identified that it is, and then that made the subject concomitant with the fin that flooded Methodology complete pedagogical pedagogical before the continuing education process, or the same way to assist the infant or consult a professional greeting specialized in the essay topic. The analysis of the results obtained allows us to identify that the teachers are in constant capacitance in order to identify ADHD and create a class that adds its own defects, and proceeds to make fun of the relatives with the fin of the continent with the shelter of the house and how to manage their behavior